(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Conversion of agricultural land into non-agricultural uses represents one of major issues of agriculture development because of its significant negative impacts on food production as well as other socio-economic and environmental aspects. Many regulations launched by the government to control wetland conversion but these policies seem ineffective. This is reflected by the decreasing wetland area for food crops cultivation. Accordingly, policies revitalization on agricultural land conversion is essential for future agricultural development. This includes: reformulation of policy orientation and policy scope, reformulation of object of the policy, improvement of policy instruments used, improvement of organization structure of policy executives, and increasing policy socialization to stakeholders.